Caracterização espaço temporal da endemicidade de hanseníase nos bairros de Aracaju, Sergipe, Brasil - Silva, Cindy Menezes (2017)
Leprosy is an infectious disease, caused by the bacillus Mycobacterium leprae, chronic, with high capacity of contagion and low capacity of people's illness. In Brazil, it is considered as a public health problem. Aracaju and several of its districts have high detection rates. Aracaju presented in 2011 a detection rate of 21.7 cases for 100 thousand inhabitants, classified as of very high endemicity. The objective of the study was to evaluate the epidemiological and spatial characteristics of leprosy through the database of the Notifiable Diseases Information System, in the Aracaju, Sergipe, Brazil neighborhoods from 2011 to 2015. This is an ecological, Retrospective study based on a secondary database of leprosy patients enrolled in the Aracaju Notification of Injury Information System from 2011 to 2015. It was used the Joinpoint Regression Program Version 4.1.1.5, Monte Carlo permutation test and increment Annual Percentage for calculations of temporal trends, besides the TerraView 4.2 program for the development of thematic maps on leprosy indicators. Besides of this, it was used spatial autocorrelation statistics such as Kernel estimation, Global Moran (I) and Local (LISA) Indexes applied to characterize spatial distribution patterns. Through [the Annual Percentage Increment was observed a gradual reduction] of less 10.2 (p <0.05) cases of the disease in the years studied. Brown color, incomplete elementary school education level, female gender and multibacillary operational classification were the most representative in general cases, and the odds ratio of the man belonged to this classification was 2.74 times higher (OR = 2 , 74, 95% CI = 1.94-3.86). The tuberculoid clinical form was more predominant among the cases and the indeterminate had a reduction of less than 19.6 (p <0.05) of the Annual Percentage Increase. The Moran global index was positive and significant (0.41, p <0.01), the cluster with the highest risk for illness and the highest density of the mean incidence of cases for Kernel estimation was located in the central and northern portion of the County. The understanding of the panorama of the geographic distribution and the profile of leprosy patients in Aracaju was relevant because it allowed a greater and better knowledge about the leprosy situation in the city.